2012
DOI: 10.5402/2012/130782
|View full text |Cite
|
Sign up to set email alerts
|

Waste Cooking Oil Biodiesel Use in Two Off-Road Diesel Engines

Abstract: This study examines the composition and combustion performance of biodiesel produced from waste cooking oil. Six fuel batches produced from waste oil used in dining-hall fryers were examined to determine their physical and chemical properties, including their elemental and fatty acid methyl ester composition. Oleic and linoleic methyl esters accounted for more than 70% of the fuel composition, while the oxygen content averaged 10.2% by weight. Exhaust emissions were monitored for 5-100% biodiesel blends using … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…The molecular composition of the neat biodiesels was determined through gas chromatography e mass spectrometry and is shown in Table 6. Cetane numbers for each fuel blend were calculated using a mass-weighted average of published individual fatty acid cetane numbers [32,33] and an assumed cetane number of 40 for ULSD. Similarly, the oxygen content of the fuel blends was estimated using weighted averages of the respective neat biodiesel and ULSD oxygen contents [31e33].…”
Section: Fuel Properties and Blend Percentage Relationshipsmentioning
confidence: 99%
“…The molecular composition of the neat biodiesels was determined through gas chromatography e mass spectrometry and is shown in Table 6. Cetane numbers for each fuel blend were calculated using a mass-weighted average of published individual fatty acid cetane numbers [32,33] and an assumed cetane number of 40 for ULSD. Similarly, the oxygen content of the fuel blends was estimated using weighted averages of the respective neat biodiesel and ULSD oxygen contents [31e33].…”
Section: Fuel Properties and Blend Percentage Relationshipsmentioning
confidence: 99%
“…A specific example is incomplete combustion [20]. The effect of this incomplete combustion is reflected in the increase of some polluting gases in tests made with biofuels in diesel engine generators, showing a reduction in HC and CO but an increase in NOx [21] and a decrease in the emission of suspended particles (PMs) and CO 2 [22]. There are many studies related to electric generators; alternative fuels have been analyzed to find the ones that offer the most significant benefits, with biodiesel considered the best alternative to meet the world's energy demands [23].…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al . reported emission characteristics of WCOME blends in two engines, Yanmar 3TN75RJ, three cylinders installed in a 1993F1145John Deere Front Mower and Yanmar 100V6‐GY single cylinder installed in a 2007 YDG 5500EVdiesel generator and concluded that blended WVOME can be used commercially without engine modification. Al‐Widyan et al .…”
Section: Introductionmentioning
confidence: 99%
“…Banerjee et al [17] synthesized WVOME by transesterification and concluded that major properties of WVOME meet the diesel fuel but due to high viscosity, it cannot be used directly in diesel engine. Guo et al [18] reported emission characteristics of WCOME blends in two engines, Yanmar 3TN75RJ, three cylinders installed in a 1993F1145John Deere Front Mower and Yanmar 100V6-GY single cylinder installed in a 2007 YDG 5500EVdiesel generator and concluded that blended WVOME can be used commercially without engine modification. Al-Widyan et al [19] synthesized WCOME and evaluated its emission and engine performance in DI diesel engine to meet ASTM specifications.…”
Section: Introductionmentioning
confidence: 99%